Does Exchange Rate Depreciation and Trade Balance Impede Economic Growth in Nigeria? - Anagun, Adeyemi Michael; Agosu, Peter Minasu (Jurnal Ilmu Ekonomi Terapan, 2024)
The Nigerian currency has experienced a significant depreciation due to its exchange with foreign currencies, particularly the dollar. This exchange rate depreciation affects purchasing power, real wages, foreign trade, debt servicing, macroeconomic stability, and interest rates. The study then seeks to fill a knowledge gap on the asymmetric link between exchange rate depreciation, trade balance, and economic growth in Nigeria. The Phillip-Perron and Augmented Dickey-Fuller unit root tests found mixed stationarity, whereas the ARDL bound cointegration test revealed a long-term link between these variables. As such, the study revealed that the depreciation of the exchange rate and trade balance positively affects economic growth. As the currency weakens, interest rates and money supply rise, and the economic growth rate rises. The study uses the error correction model to correct the disequilibrium by 59.8% to correct this economic hardship in the Nigerian economy, demonstrating that exchange rate depreciation considerably influences economic growth in the long run but not in the short term. Therefore, the practical implication is that the cost of production, importation, and inflation is high, causing fiscal restraints, governmental regulations, and economic shocks to macroeconomic stability, which may all influence economic growth. They recommend that interest rates be readjusted and that the government give grants and non-interest rate loans to small and medium enterprises to mash up with the import and export of consumable goods.